Gratitude and Warning? Methodological Considerations on a New Attempt to Balance the Historiography of the People’s Republic of Poland - Bugajewski, Maciej (Porównania, 2021)
In this article, I attempt to read a new monograph on historiography in the communist period, written by Rafał Stobiecki. The key concepts of the book are - in my opinion - gratitude and warning, spoken together. The author works on the basis of a broad understanding of the scope of research in the history of historiography. The author interprets not only (1) “research on the infrastructure of historical science”, which includes the institutional dimension of the historians’ milieu, but also (2) changes in the methodological assumptions on which historical research was based during the Polish People’s Republic and (3) the essential features of the representation of the past developed by the historiography of the People’s Republic of Poland. The author of the book emphasizes the warning, pointing to the need to evaluate the attitudes of historians. However, I focus my attention on gratitude, because it shows the achievements of our predecessors and their victories over the figures trying to subjugate them.